INCIDENCE OF NON STRUCTURAL PROTEIN (NS1) POSITIVITY & ITS CORRELATION WITH THROMBOCYTE COUNT & SERUM TRANSAMINASE LEVELS (DENGUE EPISODE-2013: A RETROSPECTIVE STUDY) - DR. MONISA KHURSHEED; KAILASH CHANDRA; D.K.SRIVASTAVA (International Journal of Pharma and Bio Sciences, 2014)
Incidence of NS-1 antigen positivity, Platelet Count, Aspartate transaminase (AST) and Alanine transaminase (ALT) levels were retrospectively analyzed in Dengue fever, post- dengue episode-2013. NS-1 was found to be positive in 64.8% cases in present episode. Significant Serum transaminasemia (raised AST and ALT levels) & thrombocytopenia were found in both NS1 + ve as well as NS-1 negative groups. Aspartate transaminase (AST) increase was more marked than alanine transaminase(ALT). Both AST & ALT showed linear increase and inverse correlation with the degree of thrombocytopenia in NS1+ve group ; however, linear correlation was lacking in the NS-1 negative group. Relatively low incidence of NS-1 positivity is indicative of high probability of dengue re-infection. Marked thrombocytopenia associated with significantly raised serum transaminase level in NS-1 negative group corroborates the possibility of secondary infection. Thus negative NS-1 antigen test report does not necessarily exclude the diagnosis of Dengue viral infection. It is recommended that Positive NS1, significant thrombocytopenia and moderately elevated AST levels within 3 – 4 days of onset of disease, may be conjointly used as distinct dengue morbidity triad for distinguishing morbid from benign patients. The criteria would help identify the patients needing hospitalization and intensified cares. However NS1 may not be relevant in endemic zones, migrants, and frequent travellers with high probability for re- infection.